Studies on the role of interleukin-1 on prostaglandin production by human fetal membranes and decidua. - Albaghdadi-Alnaif, Bunan. (University of Ottawa (Canada), 1995)
Recent studies have indicated the possible importance of cytokines in the onset of term and preterm labour. To understand this further, the effect of interleukin-1 ($\alpha$ and $\beta)$ and interleukin 6 on prostaglandin output by dispersed cells from human amnion, chorion laeve, and decidua obtained at term (38-42 weeks gestation) was examined. During the first or second 24 hours of culture, no significant effect of these interleukins on prostaglandin output was observed. The apparent refractoriness of these cells to interleukin-1 was further investigated by studying the distribution of IL-1 receptors in frozen sections of undisrupted fetal membranes and decidua at term. Whole-tissue and emulsion autoradiography indicated that receptors were present in the chorion and decidua but not in the amnion. Fresh cells labeled for IL-1 receptors confirmed the intact tissue findings. No labeling was found in the amnion; labeling was found in certain populations of the chorion cells. These studies indicate that under normal circumstances in human pregnancy at term, IL-1 does not stimulate prostaglandin production by dispersed cells. In the case of amnion, this may be due to the absence of receptors, and therefore it would appear that the IL-1 receptor must first be induced in this tissue before it can respond to this cytokine. Furthermore, although chorion laeve expresses the IL-1 receptor, dispersed cells from this tissue did not respond to the cytokine by increasing prostaglandin output. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.